2009
DOI: 10.1007/s00104-009-1692-1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications in vascular surgery

Abstract: The increase in numbers of vascular operations is due to a worldwide increase in vascular disease and diabetes. As a result of demographic changes, most of the vascular patients are comorbid and are therefore associated with multiple risk factors. Complications of vascular surgery can be divided into systemic, local non-vascular and vascular complications. Systemic complications are primarily caused by the patients' comorbidity. The prevalence of additional coronary heart disease and cerebral sclerosis account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
(61 reference statements)
0
5
0
3
Order By: Relevance
“…Postreconstructive lymphatic edema occurs in 70 to 100 % of cases, in 85 % of cases after femoro-popliteal and in 15 % after aorto-iliac bypass operations [5]. The occurrence of lymphatic fistulas in case of inguinal access site ranges from 0.8 to 18 % [6].…”
Section: Epidemiology and Definition Of Lymphatic Complicationsmentioning
confidence: 99%
“…Postreconstructive lymphatic edema occurs in 70 to 100 % of cases, in 85 % of cases after femoro-popliteal and in 15 % after aorto-iliac bypass operations [5]. The occurrence of lymphatic fistulas in case of inguinal access site ranges from 0.8 to 18 % [6].…”
Section: Epidemiology and Definition Of Lymphatic Complicationsmentioning
confidence: 99%
“…However, wound healing can occasionally be delayed by diabetes mellitus, impaired perfusion, or increased age, and can be complicated by local infections [5][6][7][8]. Animal studies have shown that VAC optimizes blood perfusion, decreases local edema by removing excess interstitial fluid, and reduces the bacterial load [9,10].…”
mentioning
confidence: 99%
“…Discussion: Treatment of vascular graft infections in peripheral bypass surgery in the absence of enFrühergebnisse nach peripherem Gefäßersatz mit einer biosynthetischen Kollagenprothese bei Protheseninfektionen Einleitung ! Die allgemeine Zunahme peripherer arteriosklerotischer Erkrankungen führt unmittelbar zu einer deutlichen Ausweitung gefäß-chirurgischer Rekonstruktionen mit alloplastischen Materialien [1]. Trotz gleichbleibender Rate an Infektionen von etwa 1 bis 6 % nimmt letztendlich die Gesamtzahl von Gefäßprothesen-infektionen deutlich zu [2].…”
unclassified
“…Die Follow-up-Untersuchungen erfolgten in 7 von 8 Fällen in der leistungserbringenden Klinik, in einem Fall wurden externe Daten zur Auswertung genutzt. Die Kodierung und Gruppierung erfolgte mit der Software "ID Diacos ® 2011 Version: 6.91".Die epidemiologischen und klinischen Daten sind in l " Tab 1. dargestellt.…”
unclassified
See 1 more Smart Citation